2020
DOI: 10.1101/2020.05.19.104307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gbx2 identifies two amacrine cell subtypes with distinct molecular, morphological, and physiological properties

Abstract: Our understanding of how the nervous sytem works is limited by our ability to identify the neuronal subtypes that comprise functional circuits. Using a genetic approach, we show that the transcription factor Gbx2 labels two amacrine cell (AC) subtypes in the mouse retina that have distinct morphological, physiological, and molecular properties. One subtype of Gbx2+ ACs are likely the previously characterized On-type GABAergic CRH-1 AC. The other Gbx2+ AC population is a previously uncharacterized non-GABAergic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(114 reference statements)
1
0
0
Order By: Relevance
“…nGnG-4 (C36) expressed Gbx2 and Lhx9. We labeled them in a Gbx2-Creer-GFP line and confirmed that both populations were GAD À and GLYT1 À , which is further supported by an independent study (Kerstein et al, 2020) Their somata were present in both the inner nuclear layer and ganglion cell layer. We additionally observed coexpression of LHX9 by immunostaining (Fig.…”
Section: Ngng Amacrinessupporting
confidence: 81%
“…nGnG-4 (C36) expressed Gbx2 and Lhx9. We labeled them in a Gbx2-Creer-GFP line and confirmed that both populations were GAD À and GLYT1 À , which is further supported by an independent study (Kerstein et al, 2020) Their somata were present in both the inner nuclear layer and ganglion cell layer. We additionally observed coexpression of LHX9 by immunostaining (Fig.…”
Section: Ngng Amacrinessupporting
confidence: 81%